Preparation method of block polymer nanoparticles

By coating pH-sensitive Eudragit S100 and chitosan in PLGA nanoparticles, the problem of high drug release rate at low pH conditions was solved, and the effect of low drug release rate in acidic environments and high drug release rate in neutral environments was achieved, and the bioavailability of quercetin was improved.

CN119656133APending Publication Date: 2025-03-21TIANJIN TUMOR HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411901505.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing nanoparticles prepared from polylactic acid-glycolic acid copolymers (PLGA) show higher drug release rates at low pH conditions, which is not conducive to the drug's stability and bioavailability in an acidic gastrointestinal environment.

Method used

The PLGA block polymer was used as the inner layer of the nanoparticles, coated with pH-sensitive polymer Eudragit S100, and used chitosan as the outer layer to reduce the drug release rate in an acidic environment.

Benefits of technology

It achieves a low drug release rate in an acidic environment and a good drug release effect in a neutral environment, which improves the bioavailability and targeted delivery ability of quercetin.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of block polymer nanoparticles. According to the invention, the quercetin and the pH-sensitive polymer are coated with the PLGA block polymer through an emulsion polymerization method, the pH-sensitive polymer is prevented from premature degradation of the nanoparticles, and the chitosan is used as the outer layer of the nanoparticles; under the combined action of the PLGA block polymer, the pH sensitive polymer and the chitosan, the drug release rate of the nano-particles when the pH value is 1.2 is reduced, so that the nano-particles have lower drug release rate and lower cytotoxicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing nanoparticles, and in particular to a method for preparing nanoparticles by using a block polymer. Background Art

[0002] Inflammatory bowel disease (IBD) is a type of chronic gastrointestinal inflammatory disease, mainly including Crohn's disease and ulcerative colitis (UC). The pathogenesis of IBD involves a complex interaction of genetic, environmental and immune factors, which in turn leads to dysregulated immune response and chronic intestinal inflammation. Existing IBD treatments are mainly aimed at reducing inflammation and maintaining remission, but are often accompanied by significant side effects and varying efficacy.

[0003] Quercetin is found in a variety of fruits and vegetables and has attracted attention for its potent anti-inflammatory, antioxidant, and immunomodulatory properties. However, its therapeutic application in IBD is limited due to its poor bioavailability and rapid degradation in the gastrointestinal environment. To overcome these challenges, researchers are exploring novel drug delivery systems to improve the stability, bioavailability, and targeted delivery of quercetin.

[0004] Polylactic-co-glycolic acid (PLGA) is a widely used biocompatible and biodegradable polymer that can provide sustained drug release and protect the encapsulated drug from premature degradation. After entering the human body, PLGA first degrades into lactic acid and glycolic acid existing in the human body, and then further degrades into carbon dioxide and water and is excreted from the body. However, nanoparticles prepared from polylactic-co-glycolic acid can be used for drug release in general environments. When under low pH conditions, the nanoparticles show a higher drug release rate, which is not conducive to the maximum effect of the drug. The present invention provides a nanoparticle with a low drug release rate in an acidic environment. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a nanoparticle having good stability, low cytotoxicity, low drug release rate in an acidic environment and good drug release effect in a neutral environment and a preparation method thereof.

[0006] The present invention adopts PLGA block polymer as the inner layer of nanoparticles, the nanoparticles are coated with pH-sensitive polymers, and chitosan is used as the outer layer to reduce the drug release rate of the nanoparticles in an acidic environment.

[0007] The present invention provides a method for preparing block polymer nanoparticles, comprising the following steps: Step (1): dissolving a certain amount of quercetin and Eudragit S100 in a solvent, dissolving PLGA-PEG, PLGA-COOH and PLGA-PLL-PEG in a solvent, and mixing the two solutions evenly with a homogenizer to obtain an oil phase solution; adding the oil phase solution dropwise to the polyvinyl alcohol aqueous phase solution, and adding ethanol to mix evenly; performing centrifugation after ultrasonic treatment, discarding the supernatant and washing with water, and storing the obtained nanoparticles at a low temperature for use.

[0008] Step (2): Chitosan is dissolved in a solvent to obtain a chitosan solution, and the nanoparticle dispersion in step (1) is added to the chitosan solution, and stirred evenly to allow chitosan to wrap around the outer surface of the nanoparticles.

[0009] Step (3): prepare a tannic acid solution, immerse the nanoparticles in the tannic acid solution in step (2), stir and mix, wash and store at 4°C for later use.

[0010] Step (4): Chitosan is dissolved in a solvent to obtain a chitosan solution, and the nanoparticles of step (3) are immersed in the chitosan solution, and washed to obtain nanoparticles with an outer layer of chitosan.

[0011] Preferably, in step (1), quercetin is dissolved in a solvent such as acetone.

[0012] Preferably, in step (1), the quercetin solution forms an oil phase solution with the PLGA-COOH, PLGA-PLL-PEG and PLGA-PEG solutions, and the volume of the oil phase solution is 1 mL-10 mL.

[0013] Preferably, in step (1), the amount of quercetin added is 2.5 mg-5 mg, the mass ratio of PLGA-PLL-PEG, PLGA-COOH and PLGA-PEG added is 1:1:3-4:1:1; and the amount of Eudragit S100 added is 5-20 mg.

[0014] Preferably, in step (1), polyvinyl alcohol forms an aqueous phase solution in water, the concentration of the aqueous phase solution is 0.5%-3% (w / v), and the volume of the aqueous phase solution is 10mL-100mL; further, protein can be added to the aqueous phase solution, and the mass ratio of protein to polyvinyl alcohol addition is 1:2; the protein can be soy protein.

[0015] Preferably, in step (1), the volume ratio of the oil phase solution to the water phase solution is 1:5-1:20.

[0016] Preferably, in step (1), the oil phase solution and the water phase solution are mixed under vacuum conditions, with a stirring speed of 500-1000 rpm and a stirring time of 12-24 h.

[0017] Preferably, in step (1), ultrasonic treatment is performed at 4° C. for 10-30 min, followed by centrifugation at 15000-25000 rpm for 15-30 min.

[0018] Preferably, in step (1), the supernatant is discarded, and the precipitate is washed multiple times with ultrapure water, and centrifuged at 15000-25000 rpm for 5 min after each wash.

[0019] Preferably, in step (2), chitosan is dissolved in acetic acid solution, the concentration of the chitosan solution is 1-3 mg / mL, the pH value of the solution is 5-6, and the concentration of the acetic acid solution is 1-2%; the chitosan solution and the nanoparticles are stirred for 1-12 hours and centrifuged at 15000-25000 rpm for 5-30 minutes.

[0020] Preferably, the chitosan in step (2) and step (4) may be carboxymethyl chitosan.

[0021] Preferably, in step (3), the concentration of the tannic acid solution is 0.5-2 mg / mL, and the immersion time is 1-6 h.

[0022] Preferably, in step (4), the concentration of the chitosan solution is 1-3 mg / mL, and the concentration of the acetic acid solution is 1-2%; and the stirring time of the chitosan solution and the nanoparticles is 1-6 h.

[0023] The present invention has the following beneficial effects: (1) The quercetin of the present invention has a good anti-inflammatory effect, but its bioavailability is poor and it is rapidly degraded in the gastrointestinal environment. Eudragit S100, as a pH-sensitive polymer, can release drugs in a targeted manner in the colon where inflammation is most severe, avoid premature degradation of the encapsulated material, and increase the release rate of quercetin in a neutral environment. The nanoparticles of the present invention have a drug release rate of more than 85% at a pH value of 7.4.

[0024] (2) The present invention self-assembles PLGA-COOH, PLGA-PEG and PLGA-PLL-PEG into shell-core structured nanoparticles in aqueous solution; the PEG block in PLGA-PEG and PLGA-PLL-PEG improves the stability, hydrophilicity and biocompatibility of the copolymer, and the increase in the hydrophilicity of the copolymer improves the drug loading capacity of hydrophilic drugs, thereby improving the drug release effect of the nanoparticles; the PLL degradation product in PLGA-PLL-PEG is an endogenous substance in the human body and will not produce significant toxicity; the length of the PLL-PEG chain segment affects the drug release, increases the drug loading capacity of hydrophilic drugs, and improves the drug release effect.

[0025] The invention selects three block polymers as the inner layer of the nanoparticles. Compared with the inner layer of a single block polymer, the drug release rate of the nanoparticles of the invention is reduced when the pH value is 1.2, so adding two additional block polymers as the inner layer of the nanoparticles is helpful to improve the drug release rate; there is an electrostatic interaction force between the amino groups in chitosan and the carboxyl groups of PLGA-COOH, PLGA-PEG and PLGA-PLL-PEG, and compared with only using PLGA-PEG, the chitosan wrapping effect of the first layer of the invention is better; tannic acid is used as a linker for the inner layer and the outer layer of the nanoparticles to improve the wrapping effect of the second layer of chitosan; further, compared with chemical crosslinking agents, the tannic acid does not produce toxicity, and the tannic acid has an anti-inflammatory effect, which is helpful to the anti-inflammatory effect of the nanoparticles; under the joint action of the block polymers, Eudragit S100 and the two layers of chitosan, the drug release rate of the nanoparticles at a pH value of 1.2 is reduced, and the release rate is about 25-30%.

[0026] (3) The present invention uses ethanol as an auxiliary reagent. After the oil phase and the water phase are mixed and stirred, ethanol is added to adjust the emulsification effect of the oil phase and the water phase. The present application uses polyvinyl alcohol and the like as emulsifiers to improve the emulsification effect of the oil phase and the water phase, thereby changing the encapsulation rate, particle size and shape of the nanoparticles. DETAILED DESCRIPTION The following is a further clear and complete description of the technical features in the technical solution provided by the present invention in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in common dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless defined as herein.

[0029] The words "preferred", "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that can provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0030] Example 1 (1) 2.5 mg of quercetin and 15 mg of Eudragit S100 were dissolved in acetone, and 9 mg of PLGA-PEG, 3 mg of PLGA-COOH and 3 mg of PLGA-PLL-PEG were dissolved in acetone. The two solutions were mixed evenly at a speed of 500 rpm to obtain an oil phase solution. 1 mL of the oil phase solution was added dropwise to 10 mL of a 2% (w / v) polyvinyl alcohol aqueous solution and stirred at a speed of 500 rpm for 12 h; after stirring for 5 min, 0.5 mL of ethanol was added and mixed evenly. After stirring, ultrasonic treatment was performed at a temperature of 4 ° C for 10 min, and centrifugation was performed at a speed of 15000 rpm for 15 min. The supernatant was discarded, and the precipitate was washed three times with ultrapure water. After each wash, centrifugation was performed at 15000 rpm for 5 min to finally obtain nanoparticles.

[0031] (2) Mix 200 mg of chitosan and 200 mL of acetic acid solution to obtain a chitosan solution, and adjust the pH value of the chitosan solution to 5. Add the nanoparticles of step (1) into the chitosan solution, and stir and mix for 6 hours to allow chitosan to wrap around the outer surface of the nanoparticles, thereby obtaining nanoparticles with chitosan as the outer layer.

[0032] (3) Prepare a tannic acid solution with a concentration of 1 mg / mL, immerse the nanoparticles in the tannic acid solution in step (2), stir and mix for 4 hours, wash and store at 4°C for later use.

[0033] (4) 300 mg of chitosan and 200 mL of acetic acid solution were mixed to obtain a chitosan solution. The nanoparticles of step (3) were immersed in the chitosan solution and stirred for 6 hours to finally obtain nanoparticles.

[0034] Example 2 (1) Dissolve 5 mg of quercetin and 15 mg of Eudragit S100 in acetone, and dissolve 5 mg of PLGA-PEG, 5 mg of PLGA-COOH, and 20 mg of PLGA-PLL-PEG in acetone. Mix the two solutions at 800 rpm to obtain an oil phase solution. Add 2 mL of the oil phase solution to 15 mL of a 3% (w / v) polyvinyl alcohol aqueous solution and stir at 800 rpm for 12 h. After stirring for 5 min, add 1 mL of ethanol and mix well. After stirring, ultrasonicate at 4 °C for 15 min and centrifuge at 15,000 rpm for 15 min. Discard the supernatant and wash the precipitate three times with ultrapure water. Centrifuge at 15,000 rpm for 5 min after each wash to obtain nanoparticles.

[0035] (2) 300 mg of chitosan and 200 mL of acetic acid solution were mixed to obtain a chitosan solution, and the pH value of the chitosan solution was adjusted to 5. The nanoparticles of step (1) were added to the chitosan solution, and the mixture was stirred for 6 h to allow the chitosan to coat the outer surface of the nanoparticles, thereby obtaining nanoparticles with chitosan as the outer layer.

[0036] (3) Prepare a tannic acid solution with a concentration of 1 mg / mL, immerse the nanoparticles in the tannic acid solution in step (2), stir and mix for 4 hours, wash and store at 4°C for later use.

[0037] (4) 400 mg of chitosan and 200 mL of acetic acid solution were mixed to obtain a chitosan solution, and the nanoparticles of step (3) were immersed in the chitosan solution and stirred for 4 hours to finally obtain nanoparticles.

[0038] Example 3 (1) 4 mg of quercetin and 15 mg of Eudragit S100 were dissolved in acetone, and 5 mg of PLGA-PEG, 10 mg of PLGA-COOH and 15 mg of PLGA-PLL-PEG were dissolved in acetone. The two solutions were mixed evenly at a speed of 600 rpm to obtain an oil phase solution. 2 mL of the oil phase solution was added dropwise to 25 mL of an aqueous solution of 2% (w / v) polyvinyl alcohol and stirred at a speed of 600 rpm for 12 h; after stirring for 5 min, 1 mL of ethanol was added and mixed evenly. After stirring, ultrasonic treatment was performed at a temperature of 4 °C for 10 min and centrifuged at a speed of 15000 rpm for 15 min. The supernatant was discarded and the precipitate was washed three times with ultrapure water. After each wash, the precipitate was centrifuged at 15000 rpm for 5 min to finally obtain nanoparticles.

[0039] (2) Mix 200 mg of chitosan and 200 mL of acetic acid solution to obtain a chitosan solution, and adjust the pH value of the chitosan solution to 5. Add the nanoparticles of step (1) into the chitosan solution, and stir and mix for 6 hours to allow chitosan to wrap around the outer surface of the nanoparticles, thereby obtaining nanoparticles with chitosan as the outer layer.

[0040] (3) Prepare a tannic acid solution with a concentration of 1 mg / mL, immerse the nanoparticles in the tannic acid solution in step (2), stir and mix for 6 hours, wash and store at 4°C for later use.

[0041] (4) 400 mg of chitosan and 200 mL of acetic acid solution were mixed to obtain a chitosan solution, and the nanoparticles of step (3) were immersed in the chitosan solution, stirred and mixed for 4 hours, and washed to obtain nanoparticles.

[0042] Comparative Example 1 Nanoparticles were prepared according to the preparation method of step (1) in Example 1, except that Eudragit S100 was not added.

[0043] Comparative Example 2 Nanoparticles were obtained according to the preparation method of step (1) in Example 1, except that the nanoparticles were not coated with two outer layers of chitosan.

[0044] Comparative Example 3 Nanoparticles were obtained according to the preparation method of steps (1) to (2) in Example 1, except that the nanoparticles in step (2) were not immersed in the tannic acid and chitosan solution.

[0045] In vitro drug release A 24-hour in vitro drug release experiment was conducted in a pH gradient medium to simulate the degradation process of nanoparticles in the gastrointestinal tract. The pH value of PBS was maintained at 1.2 for the first 2 hours, and then adjusted to 7.4 and continued for 24 hours. The release rate of the nanoparticles of Example 1 was about 25.4% at a pH value of 1.2. The release rate of the nanoparticles of Comparative Example 1 was about 53.6% at a pH value of 1.2, the release rate of the nanoparticles of Comparative Example 2 was about 38.6% at a pH value of 1.2, and the release rate of the nanoparticles of Comparative Example 3 was about 33% at a pH value of 1.2.

[0046] Cytotoxicity assay The cytotoxicity of quercetin-loaded nanoparticles on Caco-2 and SW480 cell lines was evaluated using methylthiazolyldiphenyltetrazolium bromide (MTT, Sigma-Aldrich, USA). The cytotoxicity of the nanoparticles of Examples 1-3 was detected by MTT assay. Caco-2 and SW480 cells were used, and the drug concentration range was 1 to 40 μM. Whether it was Caco-2 or SW480, the nanoparticles of Examples 1-3 were non-toxic to the cells, and the cell viability was about 100%.

[0047] The above is only a specific embodiment of the present invention and is not intended to limit the invention in other forms. Any technician familiar with the profession may use the technical content disclosed above to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing block polymer nanoparticles, characterized in that: The method for preparing nanoparticles comprises the following steps: Step (1): dissolving quercetin and Eudragit S100 in an organic solvent, dissolving PLGA-PEG, PLGA-COOH and PLGA-PLL-PEG in an organic solvent, and mixing the two solutions to obtain an oil phase solution; adding the oil phase solution dropwise to the polyvinyl alcohol aqueous phase solution, stirring for a period of time, adding ethanol and mixing evenly; after stirring, ultrasonic centrifuging, discarding the supernatant, washing with water, and finally obtaining nanoparticles; Step (2): mixing chitosan and acetic acid solution to obtain a chitosan solution; adding the nanoparticles of step (1) dropwise to the chitosan solution, stirring and mixing, so that the chitosan is wrapped around the outer surface of the nanoparticles; Step (3): preparing a tannic acid solution, and immersing the nanoparticles in step (2) in the tannic acid solution; Step (4): mixing chitosan and acetic acid solution to obtain a chitosan solution; immersing the nanoparticles in the chitosan solution, washing and obtaining nanoparticles having an outer layer of chitosan; the concentration of the chitosan solution in step (4) is higher than that in step (2).

2. The method for preparing block polymer nanoparticles according to claim 1, characterized in that: In step (1), the amount of quercetin added is 2.5 mg-5 mg, the mass ratio of PLGA-PLL-PEG, PLGA-COOH and PLGA-PEG added is 3:2:1; the amount of Eudragit S100 added is 5-20 mg.

3. The method for preparing block polymer nanoparticles according to claim 2, characterized in that: In step (1), polyvinyl alcohol is dissolved to form an aqueous solution, the concentration of the aqueous solution is 0.5%-3% (w / v), and the volume of the aqueous solution is 10mL-100mL.

4. The method for preparing block polymer nanoparticles according to claim 3, characterized in that: The volume ratio of the oil phase solution to the water phase solution in step (1) is 1:5-1:20; the oil phase solution and the water phase solution are mixed for 5 minutes and then ethanol is added; the oil phase solution and the water phase solution in step (1) are mixed with a stirring speed of 500-1000 rpm for a stirring time of 12-24 hours.

5. The method for preparing block polymer nanoparticles according to claim 4, characterized in that: In step (1), ultrasonic treatment is performed at 4° C. for 10-30 min, and then centrifugation is performed at 15000-25000 rpm for 15-30 min.

6. The method for preparing block polymer nanoparticles according to claim 5, characterized in that: In step (1), the supernatant is discarded and the precipitate is washed with ultrapure water for multiple times, and centrifuged at 15000-25000 rpm for 5 min after each wash.

7. The method for preparing block polymer nanoparticles according to claim 1, characterized in that: In step (2), the concentration of the chitosan solution is 1-3 mg / mL, and the concentration of the acetic acid solution is 1-2%; the stirring time of the chitosan solution and the nanoparticles is 1-12 h.

8. The method for preparing block polymer nanoparticles according to claim 7, characterized in that: In step (3), the concentration of the tannic acid solution is 0.5-2 mg / mL, and the immersion time is 1-6 h.

9. The method for preparing block polymer nanoparticles according to claim 8, characterized in that: In step (4), the concentration of the chitosan solution is 1-3 mg / mL, and the concentration of the acetic acid solution is 1-2%; the stirring time of the chitosan solution and the nanoparticles is 1-6 h.

10. The block polymer nanoparticles obtained by the preparation method according to any one of claims 1 to 9, characterized in that: Block polymer nanoparticles can be used to release drugs in acidic environments.